The Epidemiology of Pancreatic Cancer and the Association With Acetylsalicylic Acid in the United States: A Population-Based Study. Issue 9 (October 2020) - Khoudari, George; Alkhayyat, Motasem; Abou Saleh, Mohannad; Mansoor, Emad; Sarmini, Muhammad Talal; Baidoun, Firas; Vega, Kenneth J.; Sanaka, Madhusudhan R.
Abstract : Objectives: Pancreatic cancer (PaC) is the third leading cause of cancer-related death in the United States. Multiple studies have investigated the epidemiology and the association between PaC and acetylsalicylic acid (ASA) use, revealing mixed results. Using a large database, we sought to investigate the epidemiology of PaC. Methods: Using a commercial database (Explorys Inc, Cleveland, Ohio), which includes electronic health record data from 26 major integrated US health care systems, all patients 18 years and older diagnosed with PaC for 5 years were identified based on Systematized Nomenclature Of Medicine—Clinical Terms. We determined the prevalence of PaC and the potential associated factors using univariable and multivariable analysis. Results: Of the 32, 970, 850 individuals, we identified 30, 250 individuals with PaC with an overall prevalence of 0.08%. Individuals with PaC were more likely to be males, seniors (age, >65 years), and White, compared with patients without PaC. In subgroup analysis of chronic pancreatitis, individuals on ASA, individuals >65 years, White, and White males were less likely to have PaC, and non-White females were more likely to have PaC. Conclusions: This is the largest population-based study evaluating the epidemiology of PaC. We observed a protective association of ASA on a subgroup of patients with PaC and chronic pancreatitis.